A ação clínica do psicólogo diante do desabrigo da angústia. - Silva, Ellen Fernanda Gomes da (2018)
This thesis started from restlessness of the researcher’s clinical experiences. In her practice, the phenomenon of anguish gained evidence sometimes as a symptom to be avoided or sometimes as a fundamental affective disposition. Gradually, the anguish, as a constitutive condition and of indeterminacy originating, was becoming like “liberator” insofar as it breaks the familiarity and uncovers the ability to be more own. From this perspective, this thesis has proposed, in a general way, to understand how the clinical action of the psychologist is constituted before the phenomenon of anguish, expresses in the complaint/speech of the patient. In this edition, four psychologists were invited to describe her own experiences. The comprehensive analysis of phenomena, which were revealed in the interviews narratives and the researcher’s logbook, was carried out with the contribution of the Philosophical Hermeneutics of Gadamer. In a dialogue with hermeneutic phenomenological presuppositions, the psychologist’s practice has shown committed to receiving the affective disposition of anguish, in its ways of exhibition. For such purpose, the diagnostic and the medicalization of live were interrogated as predominant resources that cross the field of clinical practice and may obscure the existence. The intervention of the psychologist was distancing itself from theoretical- explanatory premises and getting closer to the experience in its exhibition and vigor. In this movement, it was revealed that the predictability and objectification, marks of time understanding in its own linearity, aren’t enough to provide attention and care to the demand of patients, before the situations that mobilize anguish. Lastly, the resonances of such an affective disposition were revealed directly in the clinician, indicating that the intervention is crossed by the way it understands and is mobilized by anguish. This thesis points the necessity of the clinical action, before the homelessness of anguish, sustain the obscurity of living in the world, welcoming the uprooting, the finitude, the paradoxes and the possibilities of existence; Thus opening up, other ways of responding to contemporaneous requests, without expectations and guarantee of results.